The Effect of Adding "Tape Singkong" (Fermented Cassava) Juice on the Characteristics of Fermented Milk - Aritonang, Salam N.; Roza, Elly; Novalina, Sri (Pakistan Journal of Nutrition, 2012)
This study aimed to evaluate the effect of adding “Tape Singkong” juice on the characteristic of fermented milk. In the study 4000 ml of milk was used and divided into 20 cups (200 ml/cup). A completely randomized design that consist of five treatments with four replications was used to analyze the data. The treatment are the giving tape singkong juice as much as 0% (A), 22.5% (B), 5% (C), 7.5% (D) and 10% (E) into the milk that contained 2% of Lactobacillus acidophilus. The variable was observed the characteristic of fermented milk that consist of the moisture, fat, lactose and alcohol content, acidity and bacteria colony count. The result of this research indicated that the addition of tape singkong juice up to 7.5% was significantly decreased the content of moisture, fat and lactose and increased acidity, alcohol content and bacteria colony count.